"Having a Normal Life": A Qualitative Study on Client Goal-Setting Within a Health Care and Social Needs Navigation Program. Issue 1 (January 2021) - LaForge, Kate; Wros, Peggy; Bradley, Katherine J.; Beiers-Jones, Kristen
Abstract : Client goals within healthcare and social needs navigation programs are neither well understood nor incorporated into ambulatory care practices. This study provides a qualitative analysis of client-established goals within the Interprofessional Care Access Network (I-CAN), a community-based health care and social needs navigation program. One hundred eleven client goal lists were analyzed using conventional content analysis. Twenty-two codes were developed and grouped into 4 main categories including Physical/Mental Health, Social/Social Services, Health Care System, and Daily Living. The results of this study offer insight into client goals within health care and social needs navigation programs and provide suggestions for future research.